answersLogoWhite

0


Best Answer
(-33/91) / (-3/77) =(33/91) / (3/77) = (33/91) * (77/3) = (11/91)*(77/1) =(11/13)*(11/1) = 121/13




(-33/91) / (-3/77) =(33/91) / (3/77) = (33/91) * (77/3) = (11/91)*(77/1) =(11/13)*(11/1) = 121/13




(-33/91) / (-3/77) =(33/91) / (3/77) = (33/91) * (77/3) = (11/91)*(77/1) =(11/13)*(11/1) = 121/13




(-33/91) / (-3/77) =(33/91) / (3/77) = (33/91) * (77/3) = (11/91)*(77/1) =(11/13)*(11/1) = 121/13


User Avatar

Wiki User

βˆ™ 2013-03-13 22:01:00
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

➑️
See all cards
3.75
β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…
1175 Reviews
More answers
User Avatar

Wiki User

βˆ™ 2013-03-13 22:01:00
(-33/91) / (-3/77) =(33/91) / (3/77) = (33/91) * (77/3) = (11/91)*(77/1) =(11/13)*(11/1) = 121/13


This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is division of -33 over 91 and -3 over 77?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked